Analisis Teori Performance dan Positioning dalam Komunikasi Pembangunan Berwawasan Gender - A. V. S. Hubeis; R. S. H. Mulyandari (Jurnal Komunikasi Pembangunan, 2010)
Formative and positioning theories are the critique of structuralism and critical theory. In the formative perspectiveand gender positioning, there is a consequence of the semiotic practices, as a sign of deviation patterns of adaptationand negotiation position of a subject. Participation of the performance of gender can be done through mimicry andsubversion rhetoric and understanding the intersection of gender with race, class, sexuality, ethnicity, andnationality. According to formative theory, gender or sexuality oppression is more of an ideological oppression andrepresentation. Formative and positioning theories describe the relationship between subjects, discourses, practices,and position. The development of post structuralism theory manifests a constellation of challenges and newmethodologies and adapts into a feminist critique of structuralism with methodological theory and new horizons,especially Post-Structuralism Discourse Analysis (PDA), which is directed at the meso level and the conversationfocused on understanding the structure of actions speaking (words and deeds) which is limited by reference to socialforces. PDA and then developed into a Post-Structuralism Feminist Discourse Analysis (FPDA). Forms ofparticipatory development communication perspective in the perspective of gender performance and positioningtheory state that the concept of empowerment of women in development is more focused on the patterns ofconversation, dialogue and dialectic process that includes grassroots forum for dialogue, a new function ofparticipatory communications on media, knowledge sharing on an equal footing, and Development SupportCommunication Model (DSC).